Strategic Decision to Expand Market PT Kazee Digital Indonesia from Business-to-Business (B2B) to Business-to-Consumer (B2C) - Tamara Cornelia Siallagan (Eduvest - Journal of Universal Studies, 2026)
The use of artificial intelligence (AI) and big data analytics is increasingly important in creating value in Indonesia's digital economy. PT Kazee Digital Indonesia, an AI-based analytics company that has been operating in a Business-to-Business (B2B) model for government agencies, media, and corporations for more than eight years, is now considering expansion to Business-to-Customer (B2C) due to the rapid growth of social media, the increasing role of individual content creators, and the saturation of the B2B market. This case study aims to identify challenges in the B2B–B2C transition and formulate an effective expansion strategy. The research used a mixed method, starting with in-depth interviews and internal FGDs to explore strategic motivations, risks, and decision criteria, then continued with the preparation of an Analytical Hierarchy Process (AHP) model and paired comparison questionnaires to ten internal participants from various divisions. AHP's results show that Website Development and User Experience (UX) are a top priority compared to Influencer Collaboration/KOL and Digital Education Programs. This confirms that Kazee's B2C success depends on redesigning Fastra.AI platform into an intuitive, mobile-friendly, fast value-delivering freemium interface, and featuring easy onboarding and payment systems. External collaboration remains important yet supportive once the product foundation is strong. Thus, the B2C transition is feasible with a phased approach that focuses on internal readiness, UX improvement, and strategic partnerships, while also making a theoretical contribution to the B2B–B2C transition literature and practical guidance for AI-based companies in emerging markets.